APPLICATION OF RESTORATIVE JUSTICE AS AN ALTERNATIVE TO SETTLEMENT IN CRIMINAL ACTS OF FRAUD AND EMBEZZLEMENT IN THE JURISDICTION OF SURABAYA POLICE AREA, INDONESIA - Adjie Rizky Ananda (International Journal of Innovative Technologies in Social Science, 2022)
The purpose of restorative justice in the settlement of criminal cases is to restore justice to its proper position. Both the perpetrator and the victim have apologized and agreed not to sue each other again in the future. It is hoped that the creation of peace between the perpetrator and the victim through deliberation can reduce the number of prisoners both in the Correctional Institution and in the jails; remove the stigma or stamp of criminality and return the perpetrators of crimes to the general public; criminals will be able to recognize their mistakes and not repeat their actions; and reduce the workload of the police, prosecutors, penitentiaries, courts, and penitentiaries. The fundamental problem of this research is the application of restorative justice as an option for resolving cases of fraud and embezzlement at the Surabaya Police Station, as well as obstacles in the application of restorative justice as an alternative to resolving cases of fraud and embezzlement at the Surabaya Police Station. This study uses an observational research approach in the form of a survey, namely an investigation carried out directly at the research site using data collection instruments in the form of interviews. Normative legal research is used in this article. The research findings show that: resolving criminal cases of fraud and embezzlement through restorative justice does not reduce criminal behavior. It is recommended that the sentencing policy be changed for the purpose of resolving lawsuits. The obstacle to the adoption of this restorative justice principle is the lack of an umbrella or legal foundation that is similar to both the Criminal Code and the Criminal Procedure Code since it is still governed in the internal police.